2017
DOI: 10.1080/15402002.2017.1395335
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Has Negative Implications for Children With and Without ADHD, but in Different Ways

Abstract: Poor sleep quality affects developmental subgroups in different ways. For ADHD children, poor sleep worsens their predisposed attentional deficit, while for TD children it mimics ADHD behaviors. These findings have important implications for the debate on overdiagnosis of childhood ADHD, and the use of sleep-based interventions. Above all, they highlight the importance of promoting good sleep hygiene in all children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In another study ( n = 56, not on children diagnosed with ADHD), CPT performance indicated that high reaction time scores were associated with more movements during sleep (measured through night actigraphy; Surratt et al, 2011). On similar lines, it was found that poor sleep was predictive of increased ADHD trait behaviors in a TD sample ( n = 20, 5–11 years), but were not associated with impaired attentional capacity measured through the CPT (Knight & Dimitriou, 2019). However, in the same study poor sleep (parasomnias, time in bed, sleep latency as revealed through CSHQ and actigraphy) is predictive of reduced attentional capacity in the ADHD sample ( n = 18, 5–11 years) with no predictive power toward ADHD-related behaviors, demonstrating that problems with sleep may exert impact on typically developing and clinical childhood populations in distinct ways (Knight & Dimitriou, 2019).…”
Section: Resultsmentioning
confidence: 75%
“…In another study ( n = 56, not on children diagnosed with ADHD), CPT performance indicated that high reaction time scores were associated with more movements during sleep (measured through night actigraphy; Surratt et al, 2011). On similar lines, it was found that poor sleep was predictive of increased ADHD trait behaviors in a TD sample ( n = 20, 5–11 years), but were not associated with impaired attentional capacity measured through the CPT (Knight & Dimitriou, 2019). However, in the same study poor sleep (parasomnias, time in bed, sleep latency as revealed through CSHQ and actigraphy) is predictive of reduced attentional capacity in the ADHD sample ( n = 18, 5–11 years) with no predictive power toward ADHD-related behaviors, demonstrating that problems with sleep may exert impact on typically developing and clinical childhood populations in distinct ways (Knight & Dimitriou, 2019).…”
Section: Resultsmentioning
confidence: 75%
“…Children with ADHD are often reported to have sleep problems, which in turn can further exacerbate ADHD symptoms, for example, strong correlations have been found between sleep problems in children diagnosed with ADHD and increased daytime emotional dysfunctional behavior (23). The impact of sleep problems increasing behaviors associated with ADHD is further supported by Knight and Dimitriou (24), who reported that typically developing (TD) children experiencing sleep problems scored higher on an ADHD Conners Rating Scale (25), suggesting that severe sleep problems can result in ADHD-like behaviors in TD children (24).…”
Section: Introductionmentioning
confidence: 92%
“…While sleep deprivation can lead to both daytime sleepiness and impulsivity in typically developing children (Sawyer et al, 2009), children with ADHD commonly exhibit sluggishness and hypo-vigilance, which correlates with more frequent sleep disturbances (Hvolby, 2015;Ludahl et al, 2015). These children have more severe ADHD symptoms and more functional impairments when compared to children with only ADHD or only sleep problems (Knight & Dimitriou, 2017;Sawyer et al, 2009). Inhibitory control, the ability to inhibit prepotent responses, is a core deficit of ADHD, (Barkley, 1997).…”
mentioning
confidence: 99%